PENGARUH MODEL PEMBELAJARAN ARGUMENT DRIVEN INQUIRY TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK - Dani, Ali Umar (Inspiratif Pendidikan, 2021)
This study aims to determine the effect of the Argument Driven Inquiry Learning Model on the high-order thinking ability of students at SMA 10 Gowa. The research method used is the non-equivalent pretest and posttest group design. The population in this study were all class X SMAN 10 Gowa as many as 245 students spread over 7 classes. The sampling technique was carried out by the convention sampling technique. The results showed that the students’ higher order thinking skills before using the Argument Driven Inquiry (ADI) model obtained a very low category value. The students’ higher order thinking ability after using the Argument Driven Inquiry (ADI) Model) has an average score in the very high category. There is an effect of using the Argument Driven Inquiry (ADI) learning model on higher order thinking skills.